NILAI-NILAI SHOLAWAT WAHIDIYAH DALAM MENUMBUHKAN KECERDASAN SPIRITUAL DAN AKHLAKUL KARIMAH - Fajri, Barlian; Biantoro, Oktio Frenki (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
Islamic education, especially in today's modern era, seems more inclined to develop knowledge (religious science and general science) only limited to